Perancangan Dan Pembuatan Sistem Kemudi Pada Mobil Roda Tiga - Lud Lailah Lu’lu’atul Luthfiyah; Sudiyono Sudiyono; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In the current era of globalization, technology is growing rapidly. Many people are competing in creating renewable technologies. With the in habitants expansion in the big city makes the spacious city become crowded have traffic jam everywhere. Until appears an idea to make transportation equipment that is minimalist and economical in its use, namely a three wheels car. This car will be designed to a minimum as possible and is very comfortable also has the ability to maneuver well. With the right handling system design, it will resulting a lighter, convenient, and secure driving process. To solve this problem, before making a three wheels minimalist car handling system, a design is needed first to find out the needed components for making a three wheels car using CAD (Computer Aided Design) software. In addition to the steering system, the pedal on the braking system also requires a comfortable design for the driver. The formed angle on the front wheel is 24,790. Moments on the steering system amounted to 601,32 Ncm using steel marerial ST 37. The gas pedal lever, clutch, and brake using material ASTM A 615 because the material considered strong for maximum traction quality for 560.4N.